Need Analysis for Developing English for Specific Purposes Materials for the Caregiver Program at Vocational School - Hidayati, Poppy Sofia; Herawati, Atti; Mariam, Cucu (Journal of English for Academic and Specific Purposes (JEASP), 2025)
The goal of language learning programs is to utilize language for effective communication. Due to the needs, interests, and motivations of language learners, they may show individual differences in language learning. Vocational students need English for Specific Purposes related to their fields. While based on the 2013 Indonesian English Curriculum, both senior high school and vocational learners receive the same English learning materials. Meanwhile, the English learning materials for vocational learners are supposed to be more specific in bordering certain areas. This study aimed at developing English learning materials for the caregiver program at Vocational School (SMK) Darmawan Bogor. The data was gained qualitatively by analyzing students’ needs by applying questionnaires and interviews. Learning material is then developed based on the results of the needs analysis. Furthermore, the teachers of the caregiver program reviewed the materials and they were interviewed to find out their responses. The result showed that the materials has met the learners’ needs, demands, and interests. Therefore, it can be concluded that the developed English material has met its target needs.